Work Engagement and Innovativeness in Manufacturing Sector - Wahab, Eta; Mohd Yasin Goh, Noranis (Research in Management of Technology and Business, 2022)
This research try to explore the association between work engagement and innovative work behavior in manufacturing workers. The purpose of this study is to identify the work engagement level among workers, to identify the of innovative work behavior among workers and to determine the relationship between work engagement and innovative work behavior among workers. Quantitative approach had been utilized in this study. An online survey had been conducted among 900 workers from manufacturing sectors companies in Pontian with a response rate of 58.4%. The data collected had been analyzed using both descriptive and correlation analysis by SPSS. This study found that a level of work engagement and innovative work behavior were at moderate level. This study also shows a significant association between work engagement and innovative work behavior